Pengaruh Model Project Based Learning terhadap Kemampuan Pemecahan Masalah Geografi - Raditya Ardani Hindriyanto; Sugeng Utaya; Dwiyono Hari Utomo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This study aims to determine the differences in geography problem solving abilities of students who learn using the PjBL model and students who learn to use conventional models. This research was a quasi-experimental (quasi experimental). The design of this study used a non-equivalent control group design. Data analysis in this study used one way anova with the help of SPSS 24.0. The results of this study indicate that the F-count value is 35,746 and P-value (0,000 <0.05), which means that there are significant differences in geographic problem solving ability between the control class and the experimental class. Scores of problem solving students who use the project based learning model are better than the problem solving scores of students who use conventional models. This is because the syntax in the PjBl model supports problem solving activities in Geography learning.Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan pemecahan masalah geografi siswa yang belajar menggunakan model PjBL dan siswa yang belajar menggunakan model konvensional. Penelitian ini merupakan eksperimen semu (quasi experimental). Rancangan penelitian ini menggunakan non-equivalent control group desain. Analisis data dalam penelitian ini menggunakan one way anova dengan bantuan SPSS 24.0. Hasil Penelitian ini menunjukkan nilai F-hitung 35.746 dan P-value (0.000 < 0.05) yang berarti terdapat perbedaan signifikan kemampuan pemecahan masalah geografi antara kelas kontrol dan kelas eksperimen. Skor pemecahan masalah siswa yang menggunakan model project based learning lebih baik dari skor pemecahan masalah siswa yang menggunakan model konvensional. Hal ini disebabkan karena sintak dalam model PjBL mendukung aktivitas pemecahan masalah pada pembelajaran Geografi.